Skin tumor immunity: Site does matter for antigen presentation by DCs. Issue 3 (18th February 2016) - Waithman, Jason; Gebhardt, Thomas; Bedoui, Sammy
Abstract : This commentary discusses Joncker et al. [Eur. J. Immunol. 2016. 46: 609‐618], who show that dendritic cells present tumor antigens much more efficiently when encountered in the skin rather than in the subcutaneous tissues. Abstract : The immune system has the ability to specifically identify and eliminate tumors, but the underlying mechanisms responsible for this phenomenon are not fully understood. A study published in this issue of the European Journal of Immunology now provides new insights into this important problem. Joncker et al. [Eur. J. Immunol. 2016. 46: 609‐618] show that the timely mobilization of tumor antigen‐bearing dendritic cells (DCs) from the periphery to the lymph nodes is critical for effective antitumor T‐cell immunity, and that DCs present tumor antigens much more efficiently when encountered in the skin rather than in the subcutaneous tissues.